Nuestra Madre Milpa Joven: una imagen de la totalidad efímera en un ritual wixárika - Regina Lira Larios (Journal de la Société des Américanistes)
During an agricultural ritual celebrated in a family shrine in a Wixárika community of West Mexico, an assemblage composed by artefacts, parts of sacrificed animals and persons is produced in the course of an organized sequences of acts and recognized as Our Young Mother Corn Field (Tatei Waxa ‘iimari). We will show how each of its parts is created and manipulated throughout a ritual cycle, during interactions among humans in the ritual patio and among non humans in the ritual chant, while establishing plural and contradictory same sex, cross sex and Indian and Non-Indian relations. We will show how this assemblage operates as an integrating node, while establishing the conditions for human and non-human worlds to coexist in creative act. We will thereby reflect on the modes of indigenous transmission in the links between image, time and body.